Verset en rewolusie - Wyk, I. W. C. van (Hervormde teologiese studies, 1995)
Resistance and revolution. The communion formulary of the Nederduitsch Hervonnde Kerk states clearly that a church member may not take part in revolutionary activities and that he should obey governmental authorities. Two questions are asked: 1. Does this statement imply that a Christian should obey goverments, even when they are oppressive? Can a Christian do something about his fate, or is he obliged to suffer injustice? 2. How can and must we interpret this principle today in a democratic state where resistance and rebellion are integral elements of the political process? It is argued that in Biblical Reformed theology not only the duty to obey but also the right to resist are justified. Although civil disobedience is allowed, violence is strongly condemned. This article asks the church to adhere to the communion formulary, but simultaniously to realise the vast differences between the sixteenth and the twentieth centuries.